Pengembangan Media Pembelajaran Akidah Akhlak Berbasis Tiktok untuk Meningkatkan Hasil Belajar dan Kreatifitas Siswa di Sekolah SMPS Al-Washliyah I Medan Area - Susanti, Susi; Halimah, Siti; Haidir, Haidir (Jayapangus Press, 2025)
From the initial observation on 11-10-2024 at SMPS Al-Wasliyah I Medan, the current learning process in the subject of Akidah Akhlak has been going well, because the teacher’s accuracy in choosing the model and learning media in approaching, methods, choosing teaching materials, providing media such as textbooks, interaction patterns with students and classroom management that can create a pleasant learning atmosphere. However, the learning method used by the teacher of the subject of akidah akhlak at SMPS is a method that is less varied or like in general, namely the lecture method, discussion, demonstration and memorization. The purpose of this study is to increase the effectiveness of the use of Tiktok-based Akidah Akhlak learning media in order to improve learning outcomes and student creativity at Al-Washliyah Medan School. This research method uses the Research and Development/R&D research method which is translated into Indonesian as design and development research. The results of the study stated that the TikTok application is feasible, effective and practical as a learning medium because students cannot be separated from technology and social media. It is the educator’s job to guide students to display positive things on social media and guide them to think critically when they see bad things such as videos containing negative content. Learning carried out through TikTok is able to provide good learning and is able to improve students’ critical thinking skills because it is able to attract students’ interest in carrying out learning with the conclusion of implementing Akidah Akhlak learning using a curriculum adjusted by the government. Based on data obtained from the results of extensive trials, it was found that the development of TikTok-based Akidah Akhlak learning media in addition to students being able to carry out individual and independent learning activities.